Mental models for assessing coastal social-ecological systems following disasters. (March 2021) - Furman, Kelsi L.; Aminpour, Payam; Gray, Steven A.; Scyphers, Steven B.
Abstract: Understanding abrupt change in social-ecological systems (SES), such as following major disasters, is key for restoration, adaptation, and sustainability. We describe an approach and case study using fuzzy cognitive mapping (FCM) and mental models to collectively represent local perceptions of Hurricane Irma in Key West, Florida. Using in-person FCM interviews, we sought to answer three overarching questions: 1) how did residents perceive SES relationships post-disaster, 2) how did these perceptions vary across three stakeholder groups consisting of those working in ocean recreation, resorts and inns, and non-tourism sectors, and 3) how did the aggregation of diverse opinions and perceptions affect the understanding of SES trade-offs regarding the coastal region's resilience? Across all respondents, housing was the most commonly mentioned concept occurring in 39% of all models. Coral reefs were included in 71% of ocean recreation models, whereas tourism was included in 50% of resorts and inns models. While mangroves, seawalls, and beaches were rarely to never mentioned until prompted by the interviewer, scenario analyses revealed that shorelines play an important role in residents' perceptions of how Hurricane Irma collectively impacted people and the environment. Sensitivity analyses revealed that the community, composed of a diverse representation of stakeholders, viewed core SES components similarly and trade-offs were acknowledged. Yet, different stakeholder groups perceived the SES in which they live in different ways, with each group perceiving greater damage to specific system components based on direct experience and knowledge. Our study demonstrates an approach for representing the collective perceptions of communities in post-disaster research, rebuilding, and restoration efforts. Highlights: FCM was used to study coastal social-ecological systems post-disaster. Coastal residents perceive varying shoreline types to have different values. Stakeholder models produce greater detail about specific system components. Aggregation of diverse stakeholders' knowledge produces perceptions of trade-offs.